Provide a structural model for predicting distress tolerance based on dark personality traits and perceived social support mediated by defense styles in divorce-seeking clients - Akhgary, Zahra; Ebrahimi Moghadam, Hossein; Davari, Rahim (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the presentation of a structural model for predicting distress tolerance based on dark personality traits and perceived social support mediated by defense styles in divorce-seeking clients. Method: The research method was analytical-correlation by structural equation modeling. The statistical population of the present study was the clients seeking divorce in family counseling clinics in Tehran in 2021. The sample size of 260 people was selected by available sampling method and used by Simmons and Gahr (2005) Distress Tolerance Scale, Johnson & Webster’s Dark Triangle (2010), Zimet et al.’s Multidimensional Perceived Social Support Scale (1988) and Defense Mechanism Questionnaire. Andrews et al. (1993) responded. The proposed model was then analyzed by structural equation modeling using SPSS and AMOS version 24. Results: The results showed that direct paths of personality traits and defensive styles were significant on distress tolerance (P <0.01). The direct path of perceived social support on distress tolerance was not significant (P <0.01). Direct paths of personality traits on perceived social support and defensive styles (grown and immature) on distress tolerance were significant (P <0.01), but the coefficient of personality traits was not significant on disturbed defense style (01 / 0 <P). Also, the direct paths of perceived social support on defense styles (disturbed and immature) were significant (P <0.01), but the direct path coefficient of perceived social support on the developed defense style was not significant (0.01). 0 <P). The results also showed that the indirect effects of perceived social support through the mediating role of defense styles on distress tolerance were significant (RMSEA = 0.077, GFI = 0.912, IFI = 0.959 and CFI = 0.957), but the indirect path of personality traits on distress tolerance was not significant with the mediating role of defense styles. Conclusion: Based on the findings of this study, the structural model of the modified research had a favorable and acceptable fit with the research data and this It is an important step in recognizing the factors affecting the tolerance of distress in clients seeking divorce.